Program Implementation of The Cooperative and Microenterprise Office of Jember District After The Covid 19 Pandemic Year 2023-2024 - Tectona Bambang Pradana; Edy Wahyudi; Yuslinda Dwi Handini (Green Publisher Indonesia, 2025)
The Regent of Jember Regency issued a Regent's Regulation, namely Regent's Regulation Number 21 of 2021 concerning the Position, Organizational Structure, Duties and Functions and Work Procedures of the Jember Regency Cooperative and Micro Enterprise Service. The Regent's Regulation regulates the Department of Cooperatives and Micro Enterprises which supports the development of MSMEs in Jember Regency. The Department of Cooperatives and Micro Enterprises must follow these regulations so that policies are formed with implementation in the form of programs that are followed by MSME actors. The aim of this research is to analyze the impact of the Cooperatives and Micro Enterprises Service policy based on a comparison of the objectives of the Cooperatives and Micro Enterprises Service with the direct benefits from MSME actors. This research will use qualitative research. Primary data sources will be obtained from interviews with resource persons, namely officers from the Cooperatives and Micro Enterprises Service and MSME Owners. This research uses triangulation techniques to test the validity of the data. The results of the research are that the Department of Cooperatives and Micro Enterprises is implementing programs that can support MSME actors, namely (1) On The Spot Legality Facilitation Program, (2) Vocational Training Program, (3) Go Digital MSME Entrepreneurship Program, and (4) Lawsuit Socialization Simple Free. MSME actors, namely Kopi Rengganis MSME, Opak Gulung MSME, and Aren Handycraft MSME experienced all the programs implemented.